Will electric vehicles (EVs) be less polluting than conventional automobiles under Indian city conditions?. Issue 4 (December 2020) - Sharma, Ishant; Chandel, Munish K.
Highlights: Compares emission factors for electrical vehicles and automobiles in India. Electric vehicle emissions factors for different electricity generation scenario. Criteria air pollutants and CO2 emissions analysed for Indian city conditions. Abstract: This paper compares emission factors, for four criteria pollutants: PM2.5, NOx, CO and HC, and for CO2-eq., for conventional automobiles and electric vehicles (EVs) used for passenger transport in Indian city conditions. The emissions are estimated retrospectively and prospectively for a 45-year horizon (2005–2050). For conventional vehicles, emission factors are estimated based upon the data available on the vintage and emission standards for different vehicles. For EVs, the emission factors are estimated by considering alternative Indian electricity generation mix scenarios and the amount of electricity used by the EVs. The results show that not for all the vehicle classes, the EVs are the better alternative to conventional vehicles for mitigating the emissions as in business as usual scenario of the electricity generation, in 2030, CO2 emission will decrease by at least 29% in all vehicles classes except 47% increase in electric buses. Similarly, PM2.5 emission will decrease by at least 73% in all EVs except some increase for electric cars and buses as compared to their conventional counterparts. EVs will be the most effective in air pollution reduction if they operate on more efficient batteries charged from electricity generated from renewable sources. As compared to conventional automobiles, EVs could reduce CO2 emission by 14–100% in 2050 when electricity is significantly generated from renewables.